2021
DOI: 10.3390/ijerph18094910
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of High Environmental Temperatures on Congenital Anomalies: A Systematic Review

Abstract: Links between heat exposure and congenital anomalies have not been explored in detail despite animal data and other strands of evidence that indicate such links are likely. We reviewed articles on heat and congenital anomalies from PubMed and Web of Science, screening 14,880 titles and abstracts in duplicate for articles on environmental heat exposure during pregnancy and congenital anomalies. Thirteen studies were included. Most studies were in North America (8) or the Middle East (3). Methodological diversit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Available evidence suggests that elevated temperature increases some types of congenital anomalies, such as congenital heart defects and neural tube defects [14,42,47,48]. Consistent with the recent systematic review findings on the effects of high temperatures on congenital anomalies [98], our scoping review also observed that the evidence was strongest for congenital heart defects. However, the susceptible exposure window period for congenital anomalies was less clear.…”
Section: Principal Findingssupporting
confidence: 88%
See 3 more Smart Citations
“…Available evidence suggests that elevated temperature increases some types of congenital anomalies, such as congenital heart defects and neural tube defects [14,42,47,48]. Consistent with the recent systematic review findings on the effects of high temperatures on congenital anomalies [98], our scoping review also observed that the evidence was strongest for congenital heart defects. However, the susceptible exposure window period for congenital anomalies was less clear.…”
Section: Principal Findingssupporting
confidence: 88%
“…Furthermore, this scoping review found that the current knowledge of temperaturerelated adverse maternal, foetal, and neonatal effects is dominated by findings from the USA, China, Canada, and some European countries. Additionally, consistent with other systematic reviews [98,100], minimal studies were conducted in lower-middle-income countries and low-income countries. Therefore, we do not know the effect of heat on adverse pregnancy and birth outcomes in low-income countries.…”
Section: Gaps and Recommendations For Future Researchsupporting
confidence: 80%
See 2 more Smart Citations
“…Adopting such an approach ensures that each characteristic of the patient is taken into consideration when planning treatment. BCT monitoring is important in order to prevent and reduce the risks that may occur due to heat applications in certain conditions such as pregnancy, pediatric ages, diseases affecting thermoregulatory autonomic pathways, and drug use (Leyk et al 2019;Vaidyanathan et al 2020;Haghighi et al 2021). Current balneotherapy practices involve uncertainties, for example, how to manage adverse effects from heat in pregnant patients.…”
Section: It Prevents Undesirable Conditions Due To Heat Exposurementioning
confidence: 99%